Fiqh muqaran - Abd Karim, Muhammad Hirzan Ifwad; Saari, Muhammad Arfa; Md Romzi, Muhammad Aiman Hakimi; Shaiful Azrizal, Muhammad Alif Haikal; Ahmad Jailani, Alif Ramdhan Naimullah (2025)
Slide presentation for "Fiqh muqaran"